Sửa đề: thêm (...) phần mẫu :
\(\frac{1}{x^2-3x+3}+\frac{2}{x^2-3x+4}=\frac{6}{x^2-3x+5}\\ \)
ĐK: \(x^2-3x+3\ne0\Leftrightarrow\left(x-\frac{3}{2}\right)^2+\left(3-\frac{9}{4}\right)\ne0\) có (3-9/4)>0 vậy các mẫu khác không với mọi x
Đặt x^2-3x+4=t => t>=(4-9/4)=7/4
\(\Leftrightarrow\frac{1}{t-1}+\frac{2}{t}=\frac{6}{t+1}\Leftrightarrow\frac{t\left(t+1\right)}{t\left(t-1\right)\left(t+1\right)}+\frac{2\left(t^2-1\right)}{t\left(t-1\right)\left(t+1\right)}=\frac{6t\left(t-1\right)}{t\left(t-1\right)\left(t+1\right)}\)
\(\Leftrightarrow\left(t^2+t\right)+\left(2t^2-2\right)=6t^2-6t\)\(\Leftrightarrow3t^2-7t=-2\)
\(\Leftrightarrow t^2-2.\frac{7}{6}t+\left(\frac{7}{6}\right)^2=\frac{49}{36}-\frac{2}{3}=\frac{3.49-2.36}{3.36}=\frac{49-2.12}{36}=\frac{25}{36}=\left(\frac{5}{6}\right)^2\)
\(\Leftrightarrow\left(t-\frac{7}{6}\right)^2=\left(\frac{5}{6}\right)^2\Rightarrow\left\{\begin{matrix}t=\frac{7+5}{6}=2\\t=\frac{7-5}{6}=-\frac{1}{3}\left(loai\right)\end{matrix}\right.\) 7/4<2 loại luôn
Kết luận vô nghiệm
Nhầm 7/4<2 có nghiệm
tiếp:
x^2-3x+4=2<=>x^2-3x+2=0 {a+b+c=0}
x=1 hoạc x=2
Kết luận: pt có nghiệm x=1 hoạc x=2